Innovative and flexible single screw press for the oil extraction of Calophyllum seeds - Yuli Setyo Indartono; Heriawan Heriawan; Ika Amalia Kartika (Research in Agricultural Engineering, 2019)
The oil extraction of Calophyllum seeds using a conventional single screw press leads to an inferior yield and is perceived to be less efficient as well as difficult to operate. An innovative and flexible single screw press was, therefore, designed and investigated in this study to solve these problems. Moreover, the effects of the seeds' moisture content, pressing temperature and seeds' feed rate on the oil yield and quality were identified to determine the optimal oil extraction performance from the Calophyllum seeds. The study found that the seeds' moisture content, pressing temperature and seeds' feed rate generally affected the oil yield. The yield indeed improved as the pressing temperature and the seeds' feed rate increased respectively from 45 to 75°C and 1.5 to 5 kg.h-1. The oil yield also ameliorated as the seeds' moisture content rose from 1.7 to 12.8%, but it was optimal when the seeds' moisture content was 5.5%. The best oil yield of 80.6% was, thus, obtained with the seeds' moisture content of 5.5%, a pressing temperature of 75°C and the seeds' feed rate of 5 kg per h. Although the quality of the crude oil was poor with a high viscosity (3 94 mm2.s-1) and high acid value (3 48 mg KOH/g), its density, saponification and iodine values were acceptable. After the oil refining process by degumming and neutralisation, its quality improved and met the Indonesian Biofuel Standards, except for its viscosity.